Prevalence of Bacterial Vaginosis in Females of Child Bearing Age and Utility of pH and Whiff Test in Diagnosis - Fakhar ud din, Fakhar ud din (Journal of Rawalpindi Medical College, 2020)
Objectives: To determine the prevalence of bacterial vaginosis among females of reproductive age and assessment of the effectiveness of pH and the Whiff test in its diagnosis. Methods: This was a cross-sectional study. A total of 100 subjects were included, coming with a complaint of vaginal discharge. The bacterial vaginosis was diagnosed by using the Nugent scoring system, Whiff and pH tests. The prevalence was calculated by descriptive statistics and using the Chi-square test and results were shown in percentages and mean with standard deviation. Results: The estimated prevalence of bacterial vaginosis among the local population of females of child-bearing age was found to be 39%. The mean age of females with bacterial vaginosis was 33.33±10.46 years. The Whiff test was positive in 89.74% cases, while pH was elevated in 94.87% females with bacterial vaginosis. Conclusion: Bacterial vaginosis is a frequent cause of vaginal discharge in females of reproductive age in Pakistan. The diagnosis can be easily made by using Whiff and pH tests even at resource-poor settings.